GOD’S WORDS OF RISÂLAH AND NUBUWWAH IN THE QURAN: A Thematic Study - Ibrahim, Faisal Mahmoud Adam (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
This research aims to explain the content of the divine discourse of the Prophet (PBUH) by describing the message and the prophet hood as well as directives and rules within the (call) khiṭâb for the Prophet and his ummah. The method used in this research is the inductive approach by restricting the verses in which the call is described by explaining the message and prophethood in the Holy Quran and listing the sayings of scholars and interpreters. Next, the descriptive and analytical methods are used to derive some judgments related to the verses. The research has reached conclusions that the call to describe the message and prophet hood in the Quran included on a number of rulings, including his amusement, in some places, and his command to communicate the call of God The Almighty. Some of them are related to the legislation of fighting, jihad, the rulings of prisoners, and some of them were in the matter of husbands and wives of the believers in general.